2006
DOI: 10.4049/jimmunol.177.11.8140
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy of Arthritis with TCR Isolated from the Inflamed Paw

Abstract: In recent years, the treatment of autoimmune diseases has been significantly advanced by the use of biological agents. However, some biologics are accompanied with severe side effects, including tuberculosis and other types of infection. There is thus a critical need for nonsystemic and lesion-specific methods of delivering these therapeutic agents. We attempted to treat a mouse model of arthritis by using T cells that expressed a regulatory molecule and were specifically directed to the inflamed paw. To this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 33 publications
3
38
1
Order By: Relevance
“…The experimental groups consisted of CD4 ϩ T cells from BALB/c or DO11.10 mice transduced with pMIG or pMIG-Egr2. In accordance with our previous experiments (30,31), the average transduction efficiency was Ϸ50%. The GFP-positive fraction of the transduced CD4 ϩ T cells were sorted with FACSAria and transferred to immunized mice.…”
Section: Dna Microarray Analysissupporting
confidence: 63%
See 1 more Smart Citation
“…The experimental groups consisted of CD4 ϩ T cells from BALB/c or DO11.10 mice transduced with pMIG or pMIG-Egr2. In accordance with our previous experiments (30,31), the average transduction efficiency was Ϸ50%. The GFP-positive fraction of the transduced CD4 ϩ T cells were sorted with FACSAria and transferred to immunized mice.…”
Section: Dna Microarray Analysissupporting
confidence: 63%
“…To examine the in vivo suppressive activity of Egr-2, we next performed the delayed-type hypersensitivity (DTH) reaction of BALB/c mice against chicken ovalbumin (OVA) by using T cells transduced with the Egr2 gene. The in vivo functions of T cells transduced with regulatory genes have been verified (30,31). In this experiment, CD4 ϩ T cells from BALB/c mice were transduced with pMIG or pMIG-Egr2.…”
Section: Cells Exhibit a Distinct Transcriptionalmentioning
confidence: 99%
“…In fact, recent experiments with TGF␤-induced polyclonal Tregs suggested that they were less effective than natural Tregs in ameliorating autoimmune gastritis (29). Although Ag-specific FoxP3-converted T cells failed to ameliorate arthritis to the same degree as natural Ag-specific Tregs in our hands, it is worth noting that studies carried out using a similar FoxP3-conversion technique in CIA demonstrated a significant suppression of arthritis progression (30). Furthermore, these studies identified a reduction in IL-17 transcripts within the arthritic paws of mice treated with Ag-specific FoxP3-converted T cells, however, in agreement with the data presented here, found no reduction in the draining lymph nodes.…”
Section: Discussioncontrasting
confidence: 37%
“…"switched" off by ectopic expression of foxp3, the transcription factor essential for natural Treg function? Although Tregs have received much attention because of their potential therapeutic use in autoimmune diseases, evidence suggests this will only be effective if the Treg population is specific to the relevant antigen (37)(38)(39)(40)(41). This is a problem in chronic inflammatory diseases such as RA, for which the autoantigen(s) driving disease perpetuation are not understood.…”
Section: Discussionmentioning
confidence: 99%